Safety culture in the context of operating room: nurses' perception regarding notification of errors/adverse events - Vinagre, Teresa (2019)
The notification of errors/adverse events is one of the central aspects for the quality of care and patient safety. The purpose of this pilot study is to analyse the safety culture of the operating room in relation to the errors/adverse events and their notification, in the nurses’ perception. It is a quantitative, descriptive-exploratory pilot study. A survey “Nurses’ Perception regarding Notification of Errors/Adverse Events” was applied, consisting of 8 closed questions to an intentional non-probabilistic sample consisting of 43 nurses working in the operating room of a private hospital in Lisbon. The results showed that only 51.2% of the adverse events that caused damage to patients were always notified by the nurses. Of the various adverse events occurred, 60.5% were not reported, justified by “lack of time”. There was also a negative correlation between professional experience and the frequency of error notification (p < .05). The factors referred as those that contributed most to the occurrence of errors were, pressure to work quickly (100.0%), lack of human resources (86.0%), demotivation (86.0%), professional inexperience and hourly overload (83.7%), lack of knowledge (74.4%) and communication failures (65.1%). The perception of Patient Safety was assessed by the majority of participants as “acceptable”. In conclusion, it was evident the reduced notification of adverse events in the operation room so it becomes crucial to focus on the continuous training of health professionals, as well as work on the error, to increase a safety culture with quality.